Increased epicardial adipose tissue is associated with left ventricular reverse remodeling in dilated cardiomyopathy - Yuanwei Xu; Jiajun Guo; Yangjie Li; Shiqian Wang; Ke Wan; Weihao Li; Jie Wang; Ziqian Xu; Wei Cheng; Jiayu Sun; Qing Zhang; Yuchi Han; et al. (Cardiovascular Diabetology)
Abstract Background Epicardial adipose tissue (EAT) has been suggested to play paradoxical roles in patients with heart failure. The role of EAT in dilated cardiomyopathy (DCM) patients remains unclear. We aimed to assess the associations between the dynamic changes EAT and left ventricular reverse remodeling (LVRR) in DCM patients based on baseline and follow-up CMR. Methods In this prospective study, we consecutive enrolled DCM patients with baseline and follow-up cardiac magnetic resonance (CMR) examinations. All participating patients underwent 1–2 years of guideline-directed medical therapy (GDMT) at follow-up. The EAT was measured as pericardial and epicardial fat thickness, and paracardial fat volume, while the abdominal adiposity was measured in terms of subcutaneous and visceral fat thickness. The univariable and multivariable logistic regression analyses were performed to evaluate the associations of changes in abdominal and epicardial adiposities with the presence of LVRR. Results A total of 232 patients (mean age, 45.7 ± 15.1 years, 157 male) at baseline were enrolled. After a period of GDMT with a median duration of 15.5 months (interquartile range, 12.5–19.1 months) all participants underwent follow-up CMR with the same standardized protocol. Patients who reached LVRR showed a significant increment in EAT parameters compared to those who did not. After adjusting for age, sex, and delta changes of body mass index (BMI), the increment of pericardial fat thickness (odds ratio [OR]: 1.53; 95% confidence interval [CI]: 1.27 to 1.83; p < 0.001), epicardial fat thickness (OR: 2.10; 95% CI: 1.68 to 2.63; p < 0.001), and paracardial fat volume (OR: 1.01; 95% CI: 1.01 to 1.02; p = 0.001) were significantly associated with LVRR. Conclusions In DCM patients, the CMR-derived EAT parameters increased after 1–2 years of GDMT and significantly correlated with improved ventricular structure and function, independent of changes in BMI and abdominal adiposity, which may indicate the potential protective role of EAT in DCM patients. Trial registration: URL: https://www.clinicaltrials.gov ; Unique identifier: ChiCTR1800017058. Graphical abstract